Effects of anti-gibberellin plant growth regulators on Tradescantia, Epipremnum, and Philodendron growth in interior green walls - Wiens, Lane William (Kansas State University, 2023)
Interior green walls have been growing in popularity and understanding ways to manage growth of species used in these installations. Popular plants used in green walls include species from the genera Tradescantia, Epiremnum, and Philodendron. In commercial interior green walls, plant trimming and replacement necessitated by stem elongation under low light levels is labor intensive and costly. Anti-gibberellin plant growth regulators (PGRs) may slow stem elongation and thus reduce maintenance costs in this environment. Additionally, aroid species with chartreuse leaves will darken under low light levels. With this research, we examined stem elongation and leaf darkening of these three genera through the use of anti-gibberellin plant growth regulators and differences in light levels. Two experiments were conducted with spiderworts and two were conducted with aroids. In Expt. 1, two PGRs were applied as foliar spray or drench to three spiderwort selections (zebra plant, Tradescantia zebrina and inch plant, T. fluminensis) just prior to installation in a green wall, each at three rates: ancymidol (ANC) foliar spray at 25, 100, and 200 mg•L⁻¹; paclobutrazol (PBZ) foliar spray at 20, 80 and 160 mg•L⁻¹; and PBZ drench at 1, 4, and 8 mg•L⁻¹, along with an untreated control. In Expt. 2, 80 mg•L⁻¹ PBZ foliar spray, 1 mg•L⁻¹ PBZ applied via subirrigation four times, and the combination of these two treatments, was evaluated on ‘Burgundy’ zebra plant. In both experiments, plants were placed in a vertical modular tray interior green wall. Change in total stem and specific internode length were measured every 14 days after installation for three months, the typical longevity of plants in green walls, to calculate growth per month. Anti-gibberellin application slowed internode elongation of spiderwort selections during the first month after installation. Anti-gibberellins were more effective in zebra plant at reducing overall stem growth rate and less so on inch plant. Across varieties, 25 mg•L⁻¹ foliar spray of ANC resulted in no difference in growth rate when compared to the control, though 100 to 200 mg•L⁻¹ foliar spray was effective. Based on the results of both experiments, moderate and high rates of PBZ, applied both as a foliar spray and drench, resulted in similar reduction in stem elongation. PBZ applied as 20 to 80 mg•L⁻¹ foliar spray, 4 mg•L⁻¹ drench before installation in the wall, or a combination of an 80 mg•L⁻¹ PBZ pre-installation foliar spray and recurring 1 mg•L⁻¹ via subirrigation (4 times) were effective at growth suppression of spiderworts for at least three months. Even rates of PBZ of 160 mg•L⁻¹ or 8 mg•L⁻¹ drench did not show phytotoxicity in treated plants and could be considered for use. We recommend a pre-installation foliar spray of 80 mg•L⁻¹ foliar spray or 4 mg•L⁻¹ drench for controlling stem growth across spiderwort selections. Application of anti-gibberellin PGRs to plants before installation in green walls slows stem growth and can contribute to reduced maintenance costs. Two popular aroid species used in green walls are pothos (Epipremnum aureum) and philodendron (Philodendron scandens). In two experiments, pothos ‘Neon’, pothos ‘Marble Queen’, and philodendron ‘Lemon Lime’ were evaluated. In Expt. 1, chemical treatments were a 0 mg•L⁻¹ control, 80 mg•L⁻¹ PBZ foliar spray, a 1 mg•L⁻¹ PBZ subirrigation treatment applied four times, and a combination of 80 mg•L⁻¹ PBZ and 1 mg•L⁻¹ subirrigation treatment. In Expt. 2, chemical treatments were a 0 mg•L⁻¹ control and PBZ media drenches at 4 mg•L⁻¹, 12 mg•L⁻¹, and 24 mg•L⁻¹. Light treatments of low, medium, and high levels were also included in Expt. 2. In Expt. 1, only SPAD measurements were taken to measure leaf darkening, while in Expt. 2, both stem length and SPAD measurements were taken over time. In Expt. 1, treated pothos ‘Neon’ were slightly greener than the untreated controls; however, plants in the three treatments were not different from one another. In Expt. 2, no chemical treatment slowed leaf darkening. Pothos ‘Neon’ leaf color darkened faster than philodendron ‘Lemon Lime’. Plants in the low light treatment had lighter green leaves than those in medium and high light treatments. Light level was only a significant factor during the first month of the experiment. No chemical or light treatment reduced stem length. No chemical treatment or interior light level had meaningful effects on slowing leaf darkening and managing stem length. This research demonstrates that anti-gibberellin PGRs can be useful tools to help manage stem elongation of spiderwort selections, but not in aroid plant species commonly used in green walls.
Keywords: Spiderwort; Green wall; Pothos; Philodendron; Paclobutrazol